Nationwide database analysis of insomnia, depression, and sleeping pill prescriptions in hepatocellular carcinoma patients. (3rd August 2022) - Akada, Keishi; Koyama, Noriyuki; Miura, Yuji; Aoshima, Ken
Abstract: Objective: To clarify the status of insomnia and depression and the prescription of sleeping pills in hepatocellular carcinoma (HCC) patients before and after HCC diagnosis and treatment. Methods: Patients' data from a Japanese health insurance claims database were analyzed retrospectively to determine the incidence of insomnia and depression and their association with sleeping pill prescriptions during the 6 months before and after HCC diagnosis and treatment. Results: A total of 9, 109 HCC patients (median age at diagnosis = 71.5 years, 68.1% male) were analyzed. The incidences of insomnia and depression increased significantly after HCC diagnosis. Insomnia was reported in 15.0% of patients before diagnosis, and it increased to 27.6% after diagnosis. Similarly, depression was reported in 6.3% and 11.3% before and after diagnosis, respectively. The incidences of insomnia and depression before diagnosis were higher in patients with concomitant liver diseases including hepatitis, cirrhosis, and hepatic encephalopathy. However, the rate of sleeping pill prescription was significantly lower in patients with concomitant liver diseases after diagnosis. The incidence of fracture was higher in insomnia or depression patients than others and in patients treated with sleeping pills than without before and after diagnosis. Conclusions: HCC patients had increased risks of insomnia and depression after diagnosis. The high risk of fracture in HCC patients with insomnia and depression and treated with sleeping pills suggests that it is difficult to optimize the management of HCC patients, especially those with concomitant liver diseases.